2015
DOI: 10.1002/stem.1883
|View full text |Cite
|
Sign up to set email alerts
|

The Helix-Loop-Helix Protein Id1 Controls Stem Cell Proliferation During Regenerative Neurogenesis in the Adult Zebrafish Telencephalon

Abstract: The teleost brain has the remarkable ability to generate new neurons and to repair injuries during adult life stages. Maintaining life-long neurogenesis requires careful management of neural stem cell pools. In a genome-wide expression screen for transcription regulators, the id1 gene, encoding a negative regulator of E-proteins, was found to be upregulated in response to injury. id1 expression was mapped to quiescent type I neural stem cells in the adult telencephalic stem cell niche. Gain and loss of id1 fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
107
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(120 citation statements)
references
References 56 publications
11
107
2
Order By: Relevance
“…Recent expression profiling of the lesioned spinal cord in adult zebrafish indicated a number of other microglia/macrophage related signals to be upregulated after injury, supporting a role for the immune system in spinal cord regeneration (Hui et al, 2014). It has to be noted that triggering an immune response with Zymosan is insufficient to induce expression of id1, a regulator of neurogenesis, suggesting a multitude of signals triggering regeneration (Rodriguez Viales et al, 2014).…”
Section: Types and Extent Of Neuronal Regeneration In The Cns Of Anammentioning
confidence: 99%
See 1 more Smart Citation
“…Recent expression profiling of the lesioned spinal cord in adult zebrafish indicated a number of other microglia/macrophage related signals to be upregulated after injury, supporting a role for the immune system in spinal cord regeneration (Hui et al, 2014). It has to be noted that triggering an immune response with Zymosan is insufficient to induce expression of id1, a regulator of neurogenesis, suggesting a multitude of signals triggering regeneration (Rodriguez Viales et al, 2014).…”
Section: Types and Extent Of Neuronal Regeneration In The Cns Of Anammentioning
confidence: 99%
“…Id1 function may converge on the Notch pathway as it binds to Notch downstream factors, such as Her4.1 protein (Rodriguez Viales et al, 2014).…”
Section: Reviewmentioning
confidence: 99%
“…(inhibitor of DNA binding 1, a transcription regulator), and also the estrogen-synthesizing enzyme, aromatase B (AroB), encoded by the cyp19a1b gene (Menuet et al, 2005;Tong et al, 2009;Diotel et al, 2010bDiotel et al, , 2015M€ arz et al, 2010;Dinarello, 2012;Coumailleau et al, 2015;Rodriguez Viales et al, 2015). In order to investigate the presence of 5hmC in radial glial cells, we took advantage of a cyp19a1b-GFP transgenic fish line in which GFP is expressed in radial glial cells.…”
Section: Neural Progenitors Do Not Display the 5hmc Mark In Adult Zebmentioning
confidence: 99%
“…Therefore, zebrafish models are important to elucidate mechanisms which enable neuronal regeneration. Several studies have investigated the histological changes and molecular mechanisms during regeneration in the adult zebrafish telencephalon (Diotel et al, ; Kizil, Kyritsis, et al, ; Kroehne, Freudenreich, Hans, Kaslin, & Brand, ; Kyritsis et al, ; Viales et al, ). During neuronal regeneration in telencephalon, it was shown that radial glia (RG) function as neural stem cells (Baumgart, Barbosa, Bally‐Cuif, Götz, & Ninkovic, ; Diotel et al, ; Kroehne et al, ; Kyritsis et al, ).…”
Section: Introductionmentioning
confidence: 99%